PENINGKATKAN PRESTASI BELAJAR IPA MELALUI PENERAPAN METODE DEMONSTRASI SISWA KELAS VI SD NEGERI JIMUS KECAMATAN POLANHARJO KABUPATEN KLATEN SEMESTER I TAHUN PELAJARAN 2021/2022 - Susiyanti, Susiyanti (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
This study is a report on strengthening the profesional capabilities. The purpose of this study is to improve science learning achievement through demonstration method in vegetative plant material artificial breeding to students class VI semester I SD Negeri jimus Polanharjo 2021/2022.The study consisted of two cycles and each cycles consisting of planning, implementation, observation and reflection. Subjects of this study is 12 students of class VI Sd Negeri Jimus Polanharjo 2021/2022. The collection of data through written test, documentation, interviews and observation. The result showed that the application of the method of demonstration can improve science learning achievement. In the I cycles activities mastery science learning achievement percentage of 75% or as much as 9 students, while the II cycles completeness already meet the target of 100%.The conclusion of this study is science learning achievement is increased through the application of method demonstration on plant vegetative propagation material artificial in class VI semester I SD Negeri Jimus Polanharjo.